Description of two new species of sandlances, genus Bleekeria (Perciformes, Ammodytidae) from the Andaman Sea (northeastern Indian Ocean) - Psomadakis, Peter N.; Yoshinaga, Tatsuki; Wah, Zi Za; Ida, Hitoshi (Zootaxa, 2021)
Two new species of Bleekeria Günther, 1862 are described from specimens collected in the Andaman Sea off the coast of Myanmar during bottom surveys conducted by the R/V Dr Fridtjof Nansen in 2015 and 2018. They are distinguished from each other and from congeners by a combination of morphological and meristic characters as well as fin coloration and genetic variance. Bleekeria albicauda sp. nov. has pelvic fins, 40–41 dorsal-fin rays, 54–55 total vertebrae, no teeth in jaws, 4 scale rows between dorsal-fin origin and lateral line, a single row of about 10 scales on mid-upper part of opercle, scales on central part of body clearly shorter than their height, caudal fin with white upper and lower lobes when fresh (unique within the genus). Bleekeria nigrilinea sp. nov. has no pelvic fins, 37–39 dorsal-fin rays, 49–50 total vertebrae, 2½ scale rows between dorsal-fin origin and lateral line (the smallest count within the genus with B. estuaria of Mozambique brackish water), 5–6 scales on mid-upper part of opercle arranged in a single row, scales on central part of body clearly longer than their height, upper and lower margins of caudal fin black when fresh (unique within the genus). The COI gene sequences of the two new species showed clear genetic divergence (pairwise K2P, >10 %) from Bleekeria estuaria Randall & Ida, 2014 and Bleekeria mitsukurii (Jordan & Evermann, 1902). A key to the species of Bleekeria is provided.